Innovation in Trás-os-Montes traditional products: consumer perception on extra-long maturation goat cheese - Mendonça, Álvaro (2018)
﻿Traditional agricultural and agri-food products are at the center of attention as instruments for enhancing agricultural and rural development. These products are seen as a central element in space planning, landscape preservation and nature conservation, and in combating depopulation of poor rural areas (Tibério et al., 2008). This research was based on data from a survey on the consumption preferences of goat cheese from Trás-os-Montes region, Portugal. The study was developed within the ProDeR Project - PA 49.481, measure 4.1 - Cooperation for Innovation - Development of “Serrana” goat cheese with extra-long maturation as a result of a partnership between a research unit and a cooperative. The objectives of the study were to identify the consumer profile, cheese consumption habits and to compare consumers' perception about the characteristics of cheeses with different maturation periods (2, 7 and 12 months).